Enactive account of pretend play and its application to therapy - Rucinska, Zuzanna; Reijmers, Ellen (Frontiers in Psychology, 2015)
This paper informs therapeutic practices that use play, by providing a non-standard philosophical account of pretense: the enactive account of pretend play (EAPP). The EAPP holds that pretend play activity need not invoke mental representational mechanisms; instead, it focuses on interaction and the role of affordances in shaping pretend play activity. One advantage of this re-characterization of pretense is that it may help us better understand the role of shared meanings and interacting in systemic therapies, which use playing to enhance dialog in therapy rather than to uncover hidden meanings. We conclude with bringing together findings from therapeutic practice and philosophical considerations.